EDC Machine Implementation Model in Traditional Market As Shopping Tourism Icon in Yogyakarta - Irdana, Nuryuda; Widodo, Tri; Kuntoro Priyambodo, Tri; Achjari, Didi (KnE Social Sciences, 2019)
Nowadays, in the technology and global era, people need easiness and simplicity in all things, including in financial transaction. One of the facilities which support financial transaction is banking EDC machine. Many banking companies are already deploying EDC machines in traditional market merchants. There is a traditional market that relatively big and already known as shopping tourism icon in Yogyakarta, that is Beringharjo. The number of transactions and sales volume that occur in this market is estimated reach out until billion rupiahs. However, there are some merchants that still enjoy doing transaction by cash and reluctant to use the EDC machine because of the same reasons. The aims of this research are 1) To find out the criteria that prioritized by merchants as considerations to use EDC machine 2)To construct the EDC machine implementation model at Yogyakarta shopping tourism traditional market. The model used in this research is the AHP (Analytical Hierarchy Process) model. The result of this research shows us that the order of criteria or factors that influence the traditional merchants’ acceptance of the use of EDC (Electronic Data Capture) machines in traditional shopping tourism icons in Yogyakarta are security, usability, and convenience where the security factor has the greatest weight. The analysis shows that overall, the merchant will consider the security, usability and convenience criteria based on the sub-criteria with the following weighting order; Turnover, Age, Features and shape of the machine, Technical training on machine use, Personal attitude/opinion, Socialization from related institutions, Influence of others.